An appraisal of the agricultural credit situation in Barangay Gacao, Palo, Leyte - Navarrete, Ma. Luz P. (Ma. Luz P. Navarrete, 1979)
To boost agricultural production and subsequently to raise farm incomes and upgrade living standard, problems of credit extension must be dealt with effectively. To this end, this study aims to provide credit agencies, students, etc., insights on the actual credit situations and experiences of farmers.